Hf-W thermochronometry: Closure temperature and constraints on the accretion and cooling history of the H chondrite parent body - Kleine, T; Touboul, M; Van Orman, J; Bourdon, B; Maden, C; Mezger, K; Halliday, A (2008)
We obtained Hf-W metal-silicate isochrons for several H chondrites of petrologic types 4, 5, and 6 to constrain the accretion and high-temperature thermal history of the H chondrite parent body. The silicate fractions have 180Hf/184W ratios up to ∼ 51 and 182W/184W ratios up to ∼ 33 ε units higher than the whole-rock. These high 180Hf/184W and radiogenic W isotope ratios result in highly precise Hf-W ages. The Hf-W ages of the H chondrites become younger with increasing metamorphic grade and range from ΔtCAI = 1.7 ± 0.7 Ma for the H4 chondrite Ste. Marguerite to ΔtCAI = 9.6 ± 1.0 Ma for the H6 chondrites Kernouvé and Estacado. Closure temperatures for the Hf-W system in H chondrites were estimated from numerical simulations of W diffusion in high-Ca pyroxene, the major host of radiogenic 182W in H chondrites, and range from 800 ± 50 °C for H4 chondrites to 875 ± 75 °C for H6 chondrites. Owing to these high closure temperatures, the Hf-W system closed early and dates processes associated with the earliest evolution of the H chondrite parent body. Consequently, the high-temperature interval of ∼ 8 Ma as defined by the Hf-W ages is much shorter than intervals obtained from Rb-Sr and Pb-Pb dating. For H4 chondrites, heating on the parent body probably was insufficient to cause W diffusion in high-Ca pyroxene, such that the Hf-W age of ΔtCAI = 1.7 ± 0.7 Ma for Ste. Marguerite was not reset and most likely dates chondrule formation. This is consistent with Al-Mg ages of ∼ 2 Ma for L and LL chondrules and indicates that chondrules from all ordinary chondrites formed contemporaneously. The Hf-W ages for H5 and H6 chondrites of ΔtCAI = 5.9 ± 0.9 Ma and ΔtCAI = 9.6 ± 1.0 Ma correspond closely to the time of the thermal peak within the H chondrite parent body. Combined with previously published chronological data the Hf-W ages reveal an inverse correlation of cooling rate and metamorphic grade: shortly after their thermal peak H6 chondrites cooled at ∼ 10 °C/Ma, H5 chondrites at ∼ 30 °C/Ma and H4 chondrites at ∼ 55 °C/Ma. These Hf-W age constraints are most consistent with an onion-shell structure of the H chondrite parent body that was heated internally by energy released from 26Al decay. Parent body accretion started after chondrule formation at 1.7 ± 0.7 Ma and probably ended before 5.9 ± 0.9 Ma, when parts of the H chondrite parent body already had cooled from their thermal peak. The well-preserved cooling curves for the H chondrites studied here indicate that these samples derive from a part of the H chondrite parent body that remained largely unaffected by impact disruption and reassembly but such processes might have been important in other areas. The H chondrite parent body has a 180Hf/184W ratio of 0.63 ± 0.20, distinctly lower than the 180Hf/184W = 1.21 ± 0.06 of carbonaceous chondrite parent bodies. This difference reflects Hf-W fractionation within the first ∼ 2 Ma of the solar system, presumably related to processes in the solar nebula. © 2008 Elsevier B.V. All rights reserved.